A New Role for the HTLV-1 p8 Protein: Increasing Intercellular Conduits and Viral Cell-to-Cell Transmission - Olivier Schwartz (Viruses, 2011)
Retroviruses like HIV-1 and HTLV-1 can be transmitted efficiently by direct contact between infected and target cells. For HIV-1, various modes of cell-to-cell transfer have been reported, including virological synapses, polysynapses, filopodial bridges, and nanotube-like structures. So far, only synapses and biofilms have been described for HTLV-1 transmission. Recently, Van Prooyen et al. [1] identified an additional mode of HTLV-1 transmission through cellular conduits induced by the viral accessory protein p8.